IL-10 and ET-1 as biomarkers of rheumatic valve disease - Leão,Sydney Correia (2014)
Objective: To evaluate the immunological profile and gene expression of endothelin-1 (ET-1) in mitral valves of patients with rheumatic fever originated from a reference service in cardiovascular surgery. Methods: This was a quantitative, observational and cross-sectional study. Thirty-five subjects (divided into four groups) participated in the study, 25 patients with chronic rheumatic heart disease and ten control subjects. The mean age of the sample studied was 34.5 years. Seventeen of them (48.58%) were male and 18 (51.42%) were female. Inflammatory cytokines (TNF-α, IL-4 and IL-10) were measured and ten mitral valves of patients who underwent first valve replacement were collected for determination of gene expression of endothelin-1 by real time PCR. Results: Among the groups studied (patients vs. controls), there was a statistically significant difference in IL-10 levels (P=0.002), and no differences in other cytokines. Expression of endothelin-1 was observed in 70% of samples. Quantitatively, average of ET-1 expression was 62.85±25.63%. Conclusion: Inflammatory cytokine IL-10 participates in the maintenance of chronicity of rheumatic fever in patients who underwent valve replacement and those who are undergoing medical treatment. The expression of endothelin-1 in heart valve lesions in patients undergoing mitral valve replacement confirms its association with inflammatory activity in rheumatic fever.